SUSTAINABLE FARMING THROUGH COMMUNITY EFFORTS: THE IMPACT OF ORGANIC COMPOSTING IN KUWON VILLAGE, MAGETAN REGENCY, INDONESIA - Darsin, Mahros; Basuki, Hari Arbiantara; Djumhariyanto, Dwi; Yudistiro, Danang; Wibowo, Robertoes Koekoeh Koentjoro; Elhamzah, Denaldy Elza Setya; Yahya, Hafiz Indratma; Rossy, Rio Martha Febriana; Salmansyah, Dathantara; Rizal, Ahmad Ayyub Syaiful (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This paper presents a community engagement initiative in Kuwon Village, Magetan Regency, aimed at enhancing agricultural productivity through compost production mechanization. The project, a collaboration between university researchers and local farmers, introduced organic composting techniques using a specially designed compost chopper machine. The initiative sought to address the challenges of high fertilizer costs and limited subsidized fertilizers, promoting sustainable agricultural practices and improving farmers' livelihoods. The primary goal was to provide an efficient, cost-effective method for producing organic compost, reducing dependency on chemical fertilizers, and improving soil health. The project followed a participatory approach, involving farmers at every stage—from needs assessment to design, fabrication, training, and implementation—ensuring solutions suited to the local community's needs. The compost chopper machine reduced time and labor in compost production, and farmers reported improved soil health and higher crop yields. The project also fostered community collaboration as farmers worked together to adopt new practices. Economic benefits included lower input costs and increased income from higher productivity. The success of this initiative highlights the potential of combining technological innovation with community involvement to tackle challenges faced by rural farmers in Indonesia, promoting sustainable agricultural development and improving livelihoods.